Magnetisation dynamics in magnetostrictive nanostructures - Bowe, S. R. (2017)
Spin torque oscillator devices have presented themselves as an energy efficient method of generating microwave frequencies in recent years. These are devices which rely on giant magnetoresistance to create a device resistance which oscillates at microwave frequencies due to the microwave oscillation of a magnetically free layer in the device. A spin torque oscillator can be improved by using a vortex core oscillator as the magnetically free layer offering a narrower linewidth and greater synchronisation possibilities, at the expense of a lower power output. The desire to tune the frequency of oscillation of these devices has been the focus of a great deal of research in recent years and one promising avenue of investigation is to alter the frequency of oscillation by inducing a strain anisotropy in such a device by the use of a piezoelectric transducer. In order for the induced anisotropy to be large a material must be used which exhibits a strong magnetostrictive effect such as Fe1−xGax, a material which exhibits strong magnetostrictive properties without the need for rare earth elements.